1998
DOI: 10.2166/wst.1998.0467
|View full text |Cite
|
Sign up to set email alerts
|

Importance of DOC in sediments for contaminant transport modelling

Abstract: Contaminants in the interstitial waters are not only dissolved but also associated with a filterable colloidal phase such as DOC. The DOC plays an important role regulating the distribution of chemicals between particulate and dissolved phases since it binds chemicals and makes them unavailable for vertical diffusive exchange. A three-phase partitioning model that consists of free-dissolved, DOC-bound, particulate-bound components of the chemicals involved is used for the contaminant transport model in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Burgess and others [17] have found that polychlorinated biphenyl–colloid interactions are more significant with increased core depth and presumably more reduced conditions. These workers and others [17–20] have observed higher than expected PAH concentrations in an aqueous phase containing soluble natural organic matter, which suggests the existence of PAH–organic soluble complexes. Some authors have shown a decrease in bioavailability to aquatic bluegills, guppies, and amphipods due to PAH binding with dissolved organic matter (DOM) [21–23].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Burgess and others [17] have found that polychlorinated biphenyl–colloid interactions are more significant with increased core depth and presumably more reduced conditions. These workers and others [17–20] have observed higher than expected PAH concentrations in an aqueous phase containing soluble natural organic matter, which suggests the existence of PAH–organic soluble complexes. Some authors have shown a decrease in bioavailability to aquatic bluegills, guppies, and amphipods due to PAH binding with dissolved organic matter (DOM) [21–23].…”
Section: Introductionmentioning
confidence: 77%
“…Most certainly, the drastic solution chemistry changes resulting from anaerobic conditions, especially with Ti‐citrate microcosms, affected not only PAH‐DOM solution associations, but also interactions of soluble DOM and any DOM–PAH complexes with the mineral surfaces in the soil during incubation. Other workers [17–20] have implied that increased PAH solution concentrations are the result of solution PAH‐DOM associations. It is interesting to note that whatever soil‐DOM‐PAH mechanisms are operative in the Ti‐citrate microcosm data, the degree of solubility increase was strongly influenced by PAH molecular weight (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where K d is a partition coefficient that could be related to some specific properties of the chemical, such as octanol‐water partition coefficient (K ow ) that, in turn, could be measured directly or computed as a function of contaminant solubility (S w ) and molecular weight (M); moreover, K d depends also on the organic‐carbon content of the solids (Karickhoff et al 1979; Thomann & Mueller 1987; Chapra 1997; Hwang et al 1998).…”
Section: Parameter Characterizationmentioning
confidence: 99%
“…TCDD-cumulative distribution function for log (vol). (Karickhoff et al 1979;Thomann & Mueller 1987;Chapra 1997;Hwang et al 1998).…”
Section: Parameter Characterizationmentioning
confidence: 99%